Clinical Features in Patients With PANDAS/PANS and Therapeutic Approaches: A Retrospective Study - Rea, Isabella; Guido, Cristiana Alessia; Spalice, Alberto (Frontiers in Neurology, 2021)
Objective: The clinical characteristics of patients with PANDAS (pediatric autoimmune neuropsychiatric disorders associated with streptococcal infection) and PANS (pediatric acute-onset neuropsychiatric syndrome) and the efficacy of antibiotic therapy with psychotherapy and antipsychotics were investigated to improve neurological symptoms as well as obsessive compulsive disorder (OCD). Methods: We retrospectively analyzed 62 patients with a clinical diagnosis of PANDAS/PANS enrolled from May 14, 2013 to September 15, 2020 in the Neurology Childhood Division, Department of Pediatrics at Sapienza, Rome. Clinical manifestations, neurological and psychiatric, laboratory investigations, and familiar history were collected to evaluate the differences between the two groups. The effects of various therapeutic approaches were examined. Descriptive and comparative statistical analyses were performed. Results: The mean age at onset of PANDAS/PANS symptoms was 6.2±1.2 years. The most common diagnosis was PANDAS, followed by PANS. Neurological and psychiatric symptoms were mostly evident in both groups (>70% of the population), with no significant difference between them (P=0.52 and P=0.15, respectively). Irritability, aggressivity, and food restriction were more prevalent in children with PANS than in those with PANDAS (P=0.024 and P=0.0023, respectively). The levels of anti-streptolysin O and anti-DNAse B ten-fold higher in PANDAS than those in PANS (P<0.0001). Antibiotics or psychotherapy were administered in most cases (90.3% and 53.2%, respectively), followed by antipsychotic treatments (24.2%). In the multivariate analysis, among the therapies used, psychotherapy significantly resulted in the most efficacious relief of OCD, reducing stress in patients and their parents (P=0.042). Conclusion: Our findings confirm a clear clinical difference between the two groups, PANDAS and PANS, using different approaches. In fact, irritability, aggressivity, and food restriction were significantly more frequent in children with PANS and the levels of anti-streptolysin O and anti-DNAse B were higher in PANDAS. Another relevant finding is the efficacy of psychotherapy, especially for obsessive-compulsive disorder, and of antibiotic prophylaxis in managing acute neurological symptoms.